Spinless Particles in Exponentially Varying Electric and Magnetic Fields - Kenan Sogut; Ali Havare (Advances in High Energy Physics)
We investigate the motion of the charged spin-0 particles subjected to the space-dependent electric and magnetic fields. By selecting the external fields oriented parallel and orthogonal to each other, exact solutions of the motion are obtained for the nonrelativistic and the relativistic cases. The quantized energy spectrum is determined by using the solutions obtained for the motion of the particles and dependence of the energy on the strengths of the electric and magnetic fields is discussed. We compared the energy spectrum of the nonrelativistic and the relativistic particles by using the numerical results obtained for the first few quantum levels.